2022
DOI: 10.1186/s12912-022-00950-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Knowledge, attitude and practice (KAP) of nurses on nursing Post-stroke dysphagia patients between iii-A and ii-A hospitals in China: a propensity score-matched analysis

Abstract: Background Whether knowledge, attitude and practice of nurses on nursing post-stroke dysphagia patients varies between different ranking hospitals is still unknown. This study aimed to compare the knowledge, attitude and practice level of nurses on nursing post-stroke dysphagia patients between iii-A and ii-A hospitals in China. Design A cross-sectional study design was used. Methods Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In Sichuan (China), Luo et al [18] reported that although the dysphagia attitudes and practices of geriatrics nurses were acceptable, their knowledge was low. More specifically, in post-stroke dysphagia, a study in Wuhan (China) showed that the KAP of nurses (working in neurology, neurosurgery, rehabilitation, or geriatrics departments) was low, especially in lower-grade hospitals [19]; similar results were observed in Beijing of neurological nurses [29]. Similar results regarding aspiration pneumonia KAP were observed for neurological nurses in Burkina Faso [20] and among nurses and residents in Saudi Arabia [21].…”
Section: Knowledgementioning
confidence: 59%
See 2 more Smart Citations
“…In Sichuan (China), Luo et al [18] reported that although the dysphagia attitudes and practices of geriatrics nurses were acceptable, their knowledge was low. More specifically, in post-stroke dysphagia, a study in Wuhan (China) showed that the KAP of nurses (working in neurology, neurosurgery, rehabilitation, or geriatrics departments) was low, especially in lower-grade hospitals [19]; similar results were observed in Beijing of neurological nurses [29]. Similar results regarding aspiration pneumonia KAP were observed for neurological nurses in Burkina Faso [20] and among nurses and residents in Saudi Arabia [21].…”
Section: Knowledgementioning
confidence: 59%
“…Three previous studies in China showed that the hospital level was the main factor affecting the KAP of post-stroke dysphagia in nurses [18,19,29]. In the multivariable analyses, the knowledge and attitude scores were associated with better practice scores.…”
Section: Relationship Between Knowledge Attitude and Practicementioning
confidence: 83%
See 1 more Smart Citation